2017
DOI: 10.1021/acs.jpcc.7b07129
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Mechanical Properties and Stability of Cubic Methylammonium Lead Halide Perovskites (CH3NH3PbX3, X = I, Br, Cl)

Abstract: In this study, using the density functional theory, the mechanical properties of methylammonium lead halide perovskites (CH 3 NH 3 PbX 3 , X = I, Br, Cl) were investigated. Young's modulus, bulk modulus, and shear modulus, Poisson's ratio, and many other parameters were calculated using the PBEsol and vdW approximations. Also, in this work, utilizing a new accuracy in calculating the elastic constants, the intense conflict between the previous theoretical results and the experimental data were fixed. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 57 publications
8
60
0
Order By: Relevance
“…Computational studies of the tunable properties such as electronic structures under external pressure for MAPbX 3 (X = I, Br, Cl) and all-inorganic halide perovskites CsMX 3 were reported. [91][92][93][94] Using first-principles calculations, Liu et al [95] found that CsPbI 3 under appropriate strain engineering exhibited ferroelectric and topological orders simultaneously, namely a ferroelectric topological insulator. The bulk polarization was stabilized by the metallic topological surface states, because it created an intrinsic shortcircuit condition as innate metallic electrodes, allowing automatic dissipation of surface charges.…”
Section: Effect Of Pressure and Strainmentioning
confidence: 99%
“…Computational studies of the tunable properties such as electronic structures under external pressure for MAPbX 3 (X = I, Br, Cl) and all-inorganic halide perovskites CsMX 3 were reported. [91][92][93][94] Using first-principles calculations, Liu et al [95] found that CsPbI 3 under appropriate strain engineering exhibited ferroelectric and topological orders simultaneously, namely a ferroelectric topological insulator. The bulk polarization was stabilized by the metallic topological surface states, because it created an intrinsic shortcircuit condition as innate metallic electrodes, allowing automatic dissipation of surface charges.…”
Section: Effect Of Pressure and Strainmentioning
confidence: 99%
“…Although the PCE of FA‐based PSCs has exponentially increased for several years, the basic working mechanism of PSCs has not been fully clarified. Density functional theory has been extensively used to investigate the electronic structure and other properties of various perovskite materials, with different corrections incorporated to improve agreement with the experimental data . The properties of perovskite materials can also be predicted using software, such as the Vienna Ab Initio Simulation Package and Quantum Espresso, etc.…”
Section: Properties Of Fa‐based Perovskitesmentioning
confidence: 99%
“…Density functional theory has been extensively used to investigate the electronic structure and other properties of various perovskite materials, with different corrections incorporated to improve agreement with the experimental data. [36,[74][75][76][77][78][79][80][81][82][83] The properties of perovskite materials can also be predicted using software, such as the Vienna Ab Initio Simulation Package [74] and Quantum Espresso, [76] etc.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Also, by changing the appropriate ex-correlation potential, calculated elastic constants show a 20% to 30% increment compared to elastic constants reported in previous studies. 65 The computed value of the transverse and longitudinal component of sound velocity, the average value of sound velocity and Debye temperature are summarized in Table 4. From Equations (15) to (18), the Debye temperature depends upon bulk modulus, shear modulus, and density of the material.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…Therefore, a difference of 40% to 50% has been observed with the theoretical values of Debye temperature. 43,65 The requirement of these parameters is to study the scattering of charge carrier by phonon in HOIPs.…”
Section: Elastic Propertiesmentioning
confidence: 99%